The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/0047239520984406
|View full text |Cite
|
Sign up to set email alerts
|

Time to Achieve: Implementing Blended Learning Routines in an Indian Elementary Classroom

Abstract: The purpose of this study was to investigate the effect of blended learning on students’ academic achievement, to study teachers’ perception of working in the unconventional blended atmosphere, and finally to infer on its potential in underprivileged elementary classrooms. Since this study was conducted in an unconventional set up with researchers acted as agents of change, design-based research methods were used with 50 children from a fifth standard class in an Indian elementary school. These methods include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Thus, it enhances learning engagement ( Alsalhi et al., 2021 ; Barros et al., 2017 ; Cronhjort et al., 2018 ) and improves the student learning experience ( Attard and Holmes, 2020 ; Barros et al., 2017 ; Dziuban et al., 2018 ; Jeffrey et al., 2014 ; Mumtaz et al., 2017 ; Poon, 2013 ; Rifa'i and Sugiman, 2018 ). Furthermore, several studies have shown that applying blended learning to teaching improves student academic achievement ( Alammary, 2019 ; Alsalhi et al., 2021 ; Balentyne and Varga, 2017 ; Gambari et al., 2017 ; Kundu et al., 2021 ; Lin et al., 2017 ; Poon, 2013 ; Psycharis et al., 2013 ; Zhang and Zhu, 2017 ). Several studies have confirmed that personality, learning style, and satisfaction positively affect progress in student achievement ( Cheng and Chau, 2016 ; Vasileva-Stojanovska, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it enhances learning engagement ( Alsalhi et al., 2021 ; Barros et al., 2017 ; Cronhjort et al., 2018 ) and improves the student learning experience ( Attard and Holmes, 2020 ; Barros et al., 2017 ; Dziuban et al., 2018 ; Jeffrey et al., 2014 ; Mumtaz et al., 2017 ; Poon, 2013 ; Rifa'i and Sugiman, 2018 ). Furthermore, several studies have shown that applying blended learning to teaching improves student academic achievement ( Alammary, 2019 ; Alsalhi et al., 2021 ; Balentyne and Varga, 2017 ; Gambari et al., 2017 ; Kundu et al., 2021 ; Lin et al., 2017 ; Poon, 2013 ; Psycharis et al., 2013 ; Zhang and Zhu, 2017 ). Several studies have confirmed that personality, learning style, and satisfaction positively affect progress in student achievement ( Cheng and Chau, 2016 ; Vasileva-Stojanovska, 2015 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One solution to the potential obstacles associated with this approach to teaching is found in numerous studies that have proposed methods for schools and teachers that can be applied to blended learning. According to Kundu et al. (2021) , math teaching activities and textbooks should connect to blend learning with teaching, especially as the teacher's understanding of each student's needs evolves ( Kundu et al., 2021 ; Stahl, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Graham,Allen,&Ure(2005)statedthatpeoplechooseblendedlearningforimprovedpedagogy, increasedaccessandflexibility,andcost-effectiveness. Kundu,Bej,&Dey(2021)havefoundBL effectiveinenhancingstudents'engagementandachievement.ButdoesBLaffectstudents'attitude andcreativityinanunfamiliarsetting?…”
Section: Blending Rationalesmentioning
confidence: 99%
“…The usefulness of this technology is very useful during a pandemic. During the Covid-19 pandemic, the world of education from various levels was 'forced' to adapt drastically to learning from home through online media (Kundu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%